Neural oscillatory correlates of duration maintenance in working memory. (2nd April 2015) - Chen, Y.G.; Chen, X.; Kuang, C.W.; Huang, X.T.
Graphical abstract: Highlights: The neural oscillations during maintenance of duration in WM were examined using electroencephalogram (EEG) recordings. Alpha amplitude decreased in a 4-s duration condition compared with 1-s, 2-s, and 3-s duration conditions. The amplitude of alpha power positively correlated with accuracy for the 3-s duration condition. Alpha activity is involved in duration maintenance in WM. Different internal representations are retained in WM for durations below and above about 3 s. Abstract: Working memory (WM) is a core element of temporal information processing, but little is known about the internal representation and neuronal underpinnings of the duration maintenance in WM. The neural oscillations during maintenance of duration in WM were examined using electroencephalogram (EEG) recordings. The EEG results showed that theta amplitude was not modulated by the length of duration retained in WM, while alpha amplitude decreased in a 4-s duration condition compared with 1-s, 2-s, and 3-s duration conditions. The amplitude of alpha power positively correlated with accuracy for the 3-s duration condition. The results suggest that alpha activity is involved in duration maintenance in WM. Our study provides electrophysiological evidence that different internal representations are retained in WM for durations below and above about 3 s.